1973
DOI: 10.1111/j.1365-2133.1973.tb15459.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact sensitivity to gold with unusual features

Abstract: SUMMARY A case of allergic contact sensitivity to gold is reported. In addition to the usual eczematous manifestations of allergic contact dermatitis, the patient developed a striking bilateral papular (dermal) reaction to gold ear‐rings. We suggest that both types of lesion are manifestations of allergic contact sensitivity to gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In some cases deposits of gold have been found in the skin several years after therapy (10). Occasionally granulomatous skin lesions after contact with gold items or after skin tests have been described widi features consistent with pseudoiymphoma (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases deposits of gold have been found in the skin several years after therapy (10). Occasionally granulomatous skin lesions after contact with gold items or after skin tests have been described widi features consistent with pseudoiymphoma (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…23 Papular eruption and keloid-like lesions have been noted as unusual features of gold allergy. 18,21,22 Allergic reaction to earrings presenting as itching, weeping, and soreness of the earlobe has been recognized and reported. 18 The reaction is a result of prolonged intimate contact with the dermatitis-producing metal, sometimes even after discontinuation.…”
Section: Resultsmentioning
confidence: 97%
“…18,21,22 Allergic reaction to earrings presenting as itching, weeping, and soreness of the earlobe has been recognized and reported. 18 The reaction is a result of prolonged intimate contact with the dermatitis-producing metal, sometimes even after discontinuation. The noneczematous manifestation is more prominent with gold allergy compared with the other metals.…”
Section: Resultsmentioning
confidence: 97%
“…In their review of several European studies from 1972 to 1990, Reitschel and Fowler reported nickel allergy as the most common metal allergy, with a prevalence ranging from 7.3% to 17.4%, while cobalt's prevalence was somewhat lower at 4.6% to 7.7% (2). Nickel and gold have been reported as more prevalent causes of jewelry-related sensitization (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%